2021
DOI: 10.5194/wcd-2-777-2021
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing winter climate anomalies in the Euro-Atlantic sector using circulation patterns

Abstract: Abstract. The efficacy of Euro-Atlantic circulation regimes for estimating wintertime climate anomalies (precipitation and surface temperature) over Europe is assessed. A comparison of seasonal climate reconstructions from two different regime frameworks (cluster analysis of the low-level zonal flow, and traditional blocking indices) is presented and contrasted with seasonal reconstructions using the North Atlantic Oscillation (NAO) index. The reconstructions are quantitatively evaluated using correlations and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…While the large-scale patterns derived using an EOF analysis are a good indicator of the changes in weather systems over the North Atlantic, recent works have found that jet regimes are better at capturing spatial structure compared to patterns like the NAO and have the advantage of a greater physical connection to the underlying weather systems (Madonna et al, 2021). Future work is planned to investigate how these jet regimes have varied over time in the reanalyses and how well the CMIP6 models capture these variations.…”
Section: Discussionmentioning
confidence: 99%
“…While the large-scale patterns derived using an EOF analysis are a good indicator of the changes in weather systems over the North Atlantic, recent works have found that jet regimes are better at capturing spatial structure compared to patterns like the NAO and have the advantage of a greater physical connection to the underlying weather systems (Madonna et al, 2021). Future work is planned to investigate how these jet regimes have varied over time in the reanalyses and how well the CMIP6 models capture these variations.…”
Section: Discussionmentioning
confidence: 99%
“…While the large-scale patterns derived using EOF analysis are a good indicator of the changes in weather systems over the North Atlantic, recent works have found that jet regimes are better at capturing spatial structure compared to patterns like the NAO, and have the advantage of a greater physical connection to the underlying weather systems (Madonna et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The moderate skill of winter hydrological drought forecasts might be linked to large-scale teleconnection patterns that affect European climate in winter. Some studies show that the North Atlantic Oscillation (NAO), the occurrence of blocking, and the North Atlantic jet stream are conjectured as strong predictors in winter meteorological forecasts in Europe 33,51,52 . The high skill in prediction of winter precipitation and temperature is then translated to better prediction of streamflow and subsequently streamflow drought.…”
Section: Discussionmentioning
confidence: 99%